Ethnomathematics: Two Dimensional Figure Geometry Concept in the Balla Lompoa Traditional House in South Sulawesi - Ja’faruddin Ja’faruddin; Muhammad Ammar Naufal (Institut Pendidikan Indonesia Garut, 2023)
Rumah adat Balla Lompoa merupakan bangunan adat yang dulunya digunakan sebagai istana tempat tinggal Raja Gowa. Sebagai bagian dari budaya, arsitektur tradisional dan ornamen pada Balla Lompoa berkait dengan konsep geometri yang jika digali dapat dijadikan sebagai bahan ajar. Kajian tentang konsep matematika dengan praktik budaya disebut etnomatematika. Penelitian ini merupakan penelitian deskriptif eksploratif, dengan pengumpulan data melalui observasi dan wawancara dengan salah satu penjaga rumah adat Balla Lompoa. Eksplorasi rumah adat Balla Lompoa memperlihatkan berbagai konsep geometris bangunan datar seperti bujur sangkar, bujur sangkar panjang, segitiga, lingkaran, dan belah ketupat. Bentuk bangun datar ini dapat ditemukan di Balla Lompoa dan dapat menjadi salah satu bahan ajar berupa media pembelajaran, model dan pendekatan pembelajaran serta modul menggunakan Etnomatematika.The Balla Lompoa traditional house is a traditional building once used as the palace of the King of Gowa's residence. As part of the culture, the traditional architecture, and ornaments on the Balla Lompoa connect with the concept of geometry which, if explored, can be used as teaching materials. The study of mathematical concepts with cultural practice is called Ethnomathematics. This study is a descriptive exploratory study, with data collected through observation and interviews with one of the guards of the Balla Lompoa traditional house. The exploration of the Balla Lompoa traditional house shows various geometric concepts of Two-Dimensional Figures such as squares, square Panjang, triangles, circles, and rhombuses. This flat shape can be found in the Balla Lompoa and can be one of the teaching materials in the form of learning media, teaching models and approaches and modules using Ethnomathematics.